Implementasi Standar Mutu Lulusan Pondok Pesantren Al- Busthomi Nahdlatul Watan Sampit Dan SMAS Purnama Palangka Raya - Nurmalasari, Tanti; Dakir (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
The quality of graduates is a crucial benchmark for assessing the effectiveness of educational institutions in responding to contemporary demands. This study explores the implementation of graduate quality standards at two distinct institutions: Pondok Pesantren Al-Busthomi Nahdlatul Wathan in Sampit and SMAS Purnama in Palangka Raya. Utilizing a qualitative approach with a case study design, this research highlights institutional strategies and challenges in meeting national education goals. Findings indicate that Al-Busthomi emphasizes the integration of Islamic and general education through character building, Qur'an memorization, and structured spiritual routines. In contrast, SMAS Purnama prioritizes academic excellence, digital literacy, and character education grounded in school values. Both institutions encounter obstacles such as limited teaching staff, facility gaps, and student diversity. To address these, they employ teacher training programs, character-based digital learning, and collaborative efforts with parents. This study contributes to the discourse on quality assurance in Islamic and general education by demonstrating how localized strategies can align with national education standards while accommodating contextual uniqueness.